Implementasi Kebijakan Pembangunan Pipa Transmisi Gas Bumi Cirebon-Semarang Tahap 2: Analisis Koordinasi Kelembagaan dan Fragmentasi Birokrasi - Rina Ariane; Harry Nenobais; Herry Rachmatsyah; Ferid Nugroho (PUBLICNESS: Journal of Public Administration Studies, 2026)
This study aims to analyze the implementation of the Cirebon–Semarang (CISEM) Phase 2 Natural Gas Transmission Pipeline development, identify the challenges encountered, and formulate improvement strategies. The project is designated as a National Strategic Project and plays a crucial role in integrating gas infrastructure across Java Island to support national energy security and energy transition. The research employs a descriptive qualitative approach using the Van Meter and Van Horn policy implementation framework, which consists of six key variables. Data were collected through in-depth interviews with seven key informants, field observations, and document analysis, and were examined using the interactive analysis technique. The findings indicate that policy standards and objectives have been comprehensively understood as a national priority with clearly defined technical targets. Financial support from the State Budget amounting to IDR 2.7 trillion and the use of Horizontal Directional Drilling technology serve as major supporting factors. However, implementation faces several challenges, including inter-agency bureaucratic fragmentation, differences in technical procedures, local political dynamics, limited initial technical data, and delays in high-specification material procurement, resulting in a 2–3 month schedule deviation. Overall, implementers demonstrate strong commitment, and the project positively impacts the local economy. The study recommends strengthening institutional coordination through a cross-sectoral task force to ensure project completion by March 2026.